Community Empowerment through Management of Village Funds Allocation in Indonesia - Endang Hermawan (International Journal of Science and Society, 2019)
The purpose of this study is to explore how community empowerment is carried out by village governments through village funds in village Langen Sari, West Java, Indonesia. The community empowerment is realized through Village Fund Allocation (ADD). 30% of the Village Fund Allocation is used for operational costs of the Village Government and the Village Consultative Body (BPD), 70% for community empowerment, and strengthening the capacity of the Village Government. The research method used is descriptive research with a qualitative approach using Milles and Huberman's analysis methods. The results showed that the use of Village Fund Allocation for the community empowerment component was not yet on target. Community participation is a significant factor in launching community empowerment, while a lack of human resources and weak supervision are obstacles.